Sex Differences in the Preventive Effect of Cardiovascular and Metabolic Therapeutics on Dementia - Choi, Sun Ah; Jee, Hye Jin; Bormate, Katrina Joy; Kim, Yeonjae; Jung, Yi Sook (Biomolecules and Therapeutics, 2023)
Dementia is a clinical syndrome characterized by progressive impairment of cognitive and functional abilities. As currently applied treatments for dementia can only delay the progression of dementia and cannot fundamentally cure it, much attention is being paid to reducing its incidence by preventing the associated risk factors. Cardiovascular and metabolic diseases are well-known risk factors for dementia, and many studies have attempted to prevent dementia by treating these risk factors. Growing evidence suggests that sex-based factors may play an important role in the pathogenesis of dementia. Therefore, a deeper understanding of the differences in the effects of drugs based on sex may help improve their effectiveness. In this study, we reviewed sex differences in the impact of therapeutics targeting risk factors for dementia, such as cardiovascular and metabolic diseases, to prevent the incidence and/or progression of dementia.
Keywords: Cardiovascular disease; Metabolic disease; Risk factor for dementia; Sex/gender differences; Therapeutic effect